Employees’ Attitude towards Psychological Contract in Selected Industries - Kaushal, Neelam; Ghalawat, Suman; Malik, Joginder Singh; Singh, Ajit; Kumari, Neelam (Indian Journal of Extension Education, 2020)
Psychological contract, defined as genuine but unrecorded opportunities of employees or personnel regarding the employer, plays a crucial role. Psychological Contract (PC) displays the obligations, rewards, prospective rights, etc. that an employee believes are due by the employer in exchange for the employment or job and loyalty of employees. The Psychological Contract is a vital feature of place of work relationships and the comparatively wider behavior of humans. The study examines feelings and opinions of employees regardingthe psychological contract. A survey was conducted to collect data from 245 employees of five different industries (Telecom, IT, Education, Retail, and Banking). To analyse data, statistical software SPSS- 19 was used. The findings revealed that age, experience, industry, and salary all contributed to affect psychological contract of the employees. Regarding psychological contract, gender was not found to be significant, hence the organization needs to take special care in this regard. The paper concludes with a discussion of the implications of employees’ PC for educational research and practice.